Demographic and medication characteristics of traditional Chinese medicine users among dementia patients in Taiwan: A nationwide database study. (23rd February 2015) - Lin, Shun-Ku; Tsai, Yueh-Ting; Lai, Jung-Nien; Wu, Chien-Tung
Abstract: Ethnopharmacological relevance: Few studies have reported on the utilization of traditional Chinese medicine (TCM) among dementia patients. The aim of the present study is to analyze factors associated with TCM users in the dementia populations and to investigate the medical conditions related to TCM visits. Materials and methods: A total of 18, 141 dementia patients were screened from the one million sample of the National Health Insurance Research Database. The dementia patients were then divided into TCM users and non-TCM users according to their medical records between 1997 and 2008. Demographic characteristics included gender, age, insured amount, and geographic location and medical conditions including comorbidity diseases, behavioral and psychological symptoms, and anti-dementia medication were also investigated. Their tendency of TCM usage was investigated using a multivariate logistic regression. Results: In Taiwan, 43.3% dementia patients had sought TCM treatments. The inclination of TCM usage was inversely proportional to age; the younger and early-onset dementia (age less than 55 years) patients constituted the high usage group. Female, living in central Taiwan, and higher insured amount were also associated with higher tendency of TCM use. Multilevel Poisson regression analysis showed that the Adjust odds ratios (OR) of TCM use were 1.80 (95% CI=1.68–1.94), 2.52 (95% CI=2.30–2.76), and 3.41 (95% CI=3.01–3.86) for those with one, two, three or more behavioral and psychological symptoms of dementia (BPSD), respectively compared with dementia sufferers without BPSD. In addition, polypharmacy led to higher utilization of TCM (one type: Adjust OR=1.41, 95% CI=1.28–1.56, two types: Adjust OR=1.97, 95% CI=1.63–2.00; three or more types: Adjust OR=2.95, 95% CI=2.27–2.78). More than 70% TCM visits were treated with Chinese herbal remedies, while others used acupuncture and manipulative therapies. Qi-Ju-Di-Huang-Wan (9.7%) was the most frequently prescribed formula, followed by Jia-Wei-Xiao-Yao-San and Ban-Xia-Bai-Zhu-Tian-Ma-Tang . Conclusion: More than 40% of the dementia patients in Taiwan used TCM. Young-onset dementia, higher number of BPSD, multiple chronic diseases, and polypharmacy were independent predictors for dementia patients seeking TCM medical advice. On the basis of the current findings, additional clinical or epidemiologic study on the prescription patterns of TCM in dementia treatment, or the herb-drug interaction and safety issue can be conducted. Graphical abstract: